Láhi and Attáldat: The Philosophy of the Gift and Sami Education - Kuokkanen, Rauna (The Australian Journal of Indigenous Education, 2005)
Abstract This article explores the Sami philosophy of the gift as a basis for a transformative pedagogical framework. Grounded on the Sami land-based worldview, this philosophy calls for the recognition and reciprocation of gifts, whether gifts of the land, interpersonal gifts or giftedness of an individual. In particular, the article considers two Sami concepts, that of láhi and attáldatand explains how they can serve as a framework for a Sami pedagogy that takes into account the central role of the Sami worldview in contemporary education while simultaneously critically analysing the colonial structures that continue to impact Sami society and education.